PARTICIPACIÓN COMUNITARIA Y DESARROLLO SOSTENIBLE DE LA PARROQUIA SALINAS DE GUARANDA - Gavilanéz Denisenko Daysi Alexandra (2024)
The objective of the research project was to determine how Community Participation influences the Sustainable Development of Community Tourism in the Salinas de Guaranda Parish. To this end, the methods used to promote participation in decision-making and the techniques used to promote sustainable development from an environmental, economic and social point of view were analyzed. Among the problems addressed, poor community planning was found that causes disorganization in management, poor management of resources and loss of cultural identity, as well as the lack of empowerment of the community in the application of sustainable actions that contribute to improving the quality of life of the inhabitants and to achieve real sustainable development, a clear approach is needed where the participation of each of the citizens of the different communities is promoted, with the purpose of guaranteeing that growth is inclusive and equitable. Through research, effective strategies were proposed to encourage active and meaningful participation of communities in decision-making and the implementation of sustainable development initiatives. A qualitative and quantitative methodology was used, which was based on conducting interviews and surveys with various actors involved in community participation and sustainable development of the Salinas de Guaranda Parish, to understand in depth the Participation of Communities in the Development of the Community Tourism; Based on the information obtained, the SWOT matrix was developed with the objective of designing sustainable strategies. The importance of understanding the perspectives and opinions of local communities, government authorities, environmental organizations and other relevant actors in relation to the Sustainable Development of the Parish is recognized. The results obtained will provide appropriate recommendations to strengthen community participation as a primary pillar for the sustainable development of community tourism in the Salinas de Guaranda Parish.